Genetic Basis of Male Infertility (Anwer Khan Modern Medical College Journal, 2013)
Infertility is a couple's problem. Almost 50% case males are responsible for infertility. Most common cause is oligospermia and azoospermia and approximately 5% to 15% of men with azoospermia and severe oligospermia may have a chromosomal abnormality. Men with significant spermatogenic compromise are the candidates of intracytoplasmic sperm injection (ICSI). Raised FSH level above 9 is an indication of spermatogenic compromise. So, medical treatment for these patients is waste of time and money. Early attempt of assisted reproduction is ideal to avoid the crisis of total spermatogenic failure in near future. But before going for ICSI genetic testing if possible and proper counseling about possibilities of transmission of genetic disease to offspring is necessary. DOI: http://dx.doi.org/10.3329/akmmcj.v4i1.13683 AKMMC J 2013: 4(1): 37-39